Human chromatin remodelers regulating HIV-1 transcription: a target for small molecule inhibitors - Yuan Ma; Chuan Li; Susana Valente (Epigenetics & Chromatin)
Abstract HIV-1 can establish a lifelong infection by incorporating its proviral DNA into the host genome. Once integrated, the virus can either remain dormant or start active transcription, a process governed by the HIV Tat protein, host transcription factors and the chromatin landscape at the integration site. Histone-modifying enzymes and chromatin-remodeling enzymes play crucial roles in regulating this chromatin environment. Chromatin remodelers, a group of ATP-dependent proteins, collaborate with host proteins and histone-modifying enzymes to restructure nucleosomes, facilitating DNA repair, replication, and transcription. Recent studies have highlighted the importance of chromatin remodelers in HIV-1 latency, spurring research focused on developing small molecule modulators that can either reactivate the virus for eradication approaches or induce long-term latency to prevent future reactivation. Research efforts have primarily centered on the SWI/SNF family, though much remains to be uncovered regarding other chromatin remodeling families. This review delves into the general functions and roles of each chromatin remodeling family in the context of HIV and discusses recent advances in small molecule development targeting chromatin remodelers and the HIV Tat protein, aiming to improve therapeutic approaches against HIV.